Agroforestry Research on Sodic Wasteland in Eastern Part of Uttar Pradesh - Rana, B. S.; Saxena, A. K.; Verma, S. K. (Indian Forester, 2011)
This paper deals with certain studies viz., plantation methods, nursery, growth and dry matter dynamics of Multipurpose Tree Species (MPTS) plantations, soil position and productive potential of agroforestry systems in sodic wasteland. In nursery studies, growth responses of one-year old seedlings of Dalbergia sissoo Roxb. and Acacia nilotica (Linn.) Willd. ex. Del. seedlings showed that growth and dry weight decreased as the level of sodicity and salinity increased in both species. The response breadths in case of both species were comparatively higher under sodicity levels than under salinity levels. Amongst MPTS plantations, the stand biomass for different species ranged from 81 to 171 tha-1 (Populus deltoides vs Casuarina equisetifolia). Total annual litter fall in different plantations ranged from 217 to 609 gm-2 yr-1. Under different agri-silviculture systems the grain yields of wheat and paddy were lower than that of open field condition. In case of 9-12 year old agroforestry systems, total carbon storage in biomass (above and blow ground components of trees and crops) ranged from 46.1 t C ha-1 (P. deltoides based agri-silvicultural system) to 51.9 t C ha-1 (C. equisetifolia based agri-silvicultural system). Carbon storage under C. equisetifolia- Psidium guajava based agri-silvi-horticultural system was 54.2 t C ha-1, which was highest amongst all AF systems. Amongst grasses, Pennisetum purpureum showed maximum herbage yield under Dalbergia sissoo based silvipastoral system. In a mixed tree stand, the total herbage net primary production for Brachiaria mutica was greater than that of open area. On both stands, the production was maximum during rainy season and minimum during summer. In C. equisetifolia based agri-silvi-horticultural system the fresh rhizome yield for turmeric was 8.6 t ha-1, which was greater than the yield (7.6 t ha-1) obtained in open area. There was an overall improvement in soil physico-chemical properties under agroforestry systems.